How to be content : an ancient poet's guide for an age of excess - Horace (Ancient wisdom for modern readers., 2020)
"The Roman poet Horace (65-8 BC) has long been read as a wise and pragmatic guide to living a good life. Writing at the very moment when Rome was transitioning from a republic to an empire, Romans found the advice in his poems appealing: live quietly and non-extravagantly amid the excesses of a materialistic society, avoid extreme emotions of any kind as psychologically damaging, place a value on friendship of all kinds, do not be afraid of death, and most famously live every day to the full as tomorrow may never come (carpe diem). But above all else, Horace advocated a life of contentment and self-sufficiency"--